Exploring The Potential of Zakat: Yusuf Qardhawi’s Insights for Poverty Alleviation and Economic Growth in Indonesia - Syamsuri, Syamsuri; Arief, Suyoto; Wibisono, Vina Fithriana; Fauziyah, Silva (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to explore the potential of zakat, insights from Yusuf Qardhawi perspectives for poverty alleviation and economic growth in Indonesia. This study uses a library method and descriptive analysis approach. The result of this study indicated that the management of zakat its relevance in Indonesia insight from Yusuf Qardhawi are (1) expanding the provisions of the assets that are subject to zakat funds needs to be managed productively; (2) the management and distribution of zakat in order to function properly requires centralization of zakat management by the state (government). The role of the government in alleviating poverty and economic growth includes: optimizing the performance of zakat institutions in accordance with zakat regulations; increasing public literation of zakat, encouraging social innovations as a form of efficiency and transparency in the distribution and utilization of zakat; supervising zakat institutions on the impact on poverty alleviation and maximizing the potential of zakat in improving economic growth and the welfare of underprivileged people. This study provides insight for the management of zakat in Indonesia is optimized using Yusuf Qardhawi’s concept, its relevant to poverty issues and improvisation of economic growth.